Application progress of SGX in trusted computing area - Bo ZHAO; Anqi YUAN; Yang AN (网络与信息安全学报)
The trusted computing technology SGX protects the confidentiality and integrity of key codes and data by isolating a trusted execution environment, which can help prevent all kinds of attacks.Firstly, the research background and working principle of SGX were introduced, the research status of SGX in the field of trusted computing were analyzed.Then, sorted out the current application difficulties and solutions of SGX were sorted out and compared with other trusted computing technologies.Finally, SGX technology development direction in the field of trusted computing was discussed.